PEMAHAMAN TEKS TENTANG PEREMPUAN DALAM ISLAM - Jamil, Syahril (Nurani, 2013)
Abstract: In the scope of Islamic Studies, woman’s matter has almost become controversy. One side considers woman as a second class. The other side considers as equal as man. Are three topics to be discussed in this article, namely the creating of woman, woman political role, and woman withes value? This article is intended to present philosophers different thought of woman. Through deep research, it is found that controversy occurred based on different understanding toward the religious text. One side comprehends the text in textual, the other side comprehends the text in contextual, without neglecting sociological and historical approaches of the emerging text.ملخص: وفىمجال البحث للتعـاليم الاسلأمـية، مازالـت المرأة موضوعة مشكـة عـن المـفـكـريـن. بعـضهـم يعـدونهاانـسـانا جانبيا، وبـعـضهم يك فحون المساواة بيـن الرجل والمرأة. وفىهذه المقالـة تـبحـث ثلاثمـسا ئل، وهى: اول تكويـن المرأة ودورالمرأة فىميدان السـياســة وقـيـم شـهادةالمرأة. وبعدالبحـث عـن هذهالمـسـألة بحـثـا عـميـقا، فـتـوجدالواقعة ان جذرالمـشـكـة هواخـتلأف الفهـم عـن النـصوالديـنـيـة. كان الفـريـق يـفهـمها فـهـمالفظيـا والـفـريـق الأ خريفهمها فهماسـياقـيا واطاريا بـتـقـرن الاجـتـماعـيـة والتاريخـيـة علىالنصواردة. Kata kunci: pemahaman tekstual-kontekstual, perempuan.